Predictive factors for radiographic progression of large joint damage in patients with rheumatoid arthritis treated with biological disease-modifying antirheumatic drugs (bDMARDs): Results of 3 to 4 years of follow-up. Issue 6 (2nd November 2019) - Nakajima, Arata; Terayama, Keiichiro; Sonobe, Masato; Aoki, Yasuchika; Takahashi, Hiroshi; Akatsu, Yorikazu; Taniguchi, Shinji; Yamada, Manabu; Kubota, Ayako; Nakagawa, Koichi
Abstract: Objectives: Little information is available regarding long-term follow-up of radiographic progression of damage (RPD) to large joints during treatment of rheumatoid arthritis (RA) with biological disease-modifying antirheumatic drugs (bDMARDs). We evaluated 3- to 4-year follow-up results and the associations between RPD and patient background and Larsen grade (LG) of joints. Methods: Seventy-one RA patients receiving bDMARDs for 3 to 4 years or who achieved bDMARD-free status were included. The mean age and disease duration at the start of bDMARDs were 62.4 years and 10.8 years, respectively. A total of 314 joints, including shoulders, elbows, hips, knees, and ankles, were evaluated to determine whether RPD was present by comparing radiographs before and after treatment. Results: RPD was observed in 24 patients (33.8%) and 34 joints (10.8%). Joints with an LG of III or higher had significantly higher rates of RPD than those with LGs I and II. Multivariate logistic regression analysis revealed that stage and health assessment questionnaire (HAQ) score at 18-months were independent risk factors for RPD (cut-off value: 2.5, odds ratio: 7.222 for stage; cut-off value: 0.9375, odds ratio: 6.278 for HAQ at 18-months). Conclusion: Stage, HAQ at 18-months, and LG at the start of bDMARDs were predictive of RPD after 3 to 4 years. bDMARDs should be started before both stage and LG exceed III and the therapeutic strategy should be determined so that HAQ does not exceed 1.0 during treatment.